Spatial and Temporal Variation in Deep-Sea Meiofauna at the LTER Observatory HAUSGARTEN in the Fram Strait (Arctic Ocean) - Thomas Soltwedel; Katarzyna Grzelak; Christiane Hasemann (Diversity, 2020)
Time-series studies at the LTER (Long-Term Ecological Research) observatory HAUSGARTEN have yielded the world’s longest time-series on deep-sea meiofauna and thus provide a decent basis to investigate the variability in deep-sea meiobenthic communities at different spatial and temporal scales. The main objective of the present study was to investigate whether the sediment-dwelling meiofauna (size range: 32–1000 µm) is controlled by small-scale local environmental conditions, rather than large-scale differences between water depths. Univariate and multivariate statistical analyses, including distance-based linear models (DistLM) and redundancy analysis (dbRDA), revealed that due to their small size, meiofauna tend to mainly respond to micro-scale (centimeter) variations in environmental conditions in surface and subsurface sediment layers. Inter-annual temporal patterns among metazoan meiofauna at higher taxon levels revealed only a weak effect of time, and merely on the rare meiofauna taxa (<2% of the total meiofauna community) at HAUSGARTEN.